Treaty talks [videorecording (DVD)] : paddling up the Columbia River for salmon and people - Demetrios, Xander; Wicks-Arshack, Adam (Voyages of Rediscovery, 2015)
Utilizing 5 dugout canoes crated by youth, this film follows the salmon up the Columbia River from the Pacific Ocean to the river's source, a distance of 1,234 miles. Many groups are joining forces to create ecosystem based solutions, 70 years after the Grand Coulee Dam blocked salmon in attempt to have them return to the headwaters.